Trifulca a la vista - Mitford, Nancy, 1904-1973 (Libros del Asteroide, 2012)
Eugenia Malmains is one of the richest girls in England and an ardent supporter of Captain Jack and the Union Jack shirts; Noel and Jasper are both in search of an heiress (so much easier than trying to work for the money); Poppy and Marjorie are nursing lovelorn hearts; and the beautiful bourgeois Mrs Lace is on the prowl for someone to lighten the boredom of her life. They all congregate near Eugenia's fabulous country home at Chalford, and much farce ensues.